Analysis of financial distress in banking companies listed on the indonesian stock exchange - Isnaeni Rokhayati; Sodik Dwi Purnomo; Diah Retnowati; Hari Winarto; Agus Prabawa; Heris Kencana (Faculty of Economics and Business Mulawarman University, 2022)
Financial distress is a condition when a company experiences an inability to fulfill all financial obligations in the long term. This study analyzes capital structure, female directors, liquidity, and profitability predicting the possibility of financial companies in the 2018-2020 period experiencing financial distress. The research population is financial companies operating on the IDX in the 2018-2020 period with as many as 105 companies. Determination of the sample used is purposive sampling method with the results of 46 companies. The research analysis technique is panel data regression with the best fixed effect model. Based on the analysis results show that the capital structure has a significant effect on financial distress where the higher the company's leverage will cause financial distress. While female director, liquidity, and profitability have no significant effect on the company's financial distress. It is expected that the company will always pay attention to the level of use of leverage so that it can maintain the optimal condition of the company's cash. For future research, it is possible to add variables such as inflation rate, interest rate, tax, firm size, growth sales which can affect financial distress. Â